Gender and Power Relations in Aisha Saeed’s Amal Unbound - Albi Fahri; Ida Rosida (Muslim English Literature, 2023)
This paper discusses the power relation and gender in the novel Amal Unbound by Aisha Saeed (2018). This study focuses on the four main characters, Amal, Abu, Jawad, and Baji, in which  Abu, Amal ‘s father, has a relationship that puts her as a subordinate one as well as Jawad, who has the power from his economic aspect. The restriction experienced by a female character, Amal, became a gender issue regarding the oppression of women, which must be surrendered to certain power circumstances. This research explores the power relations between female and male characters and their effect on gender. This study uses a qualitative method and applies Michel Foucault's theory of power relations and the concept of gender. The results show that Amal’s resistance is echoed in the desire to destroy the power structure that put Jawad as the highest authority holder. Amal prioritizes resistance to free her choice in her gender identity, and power relations are obliged to change with the resistance. Power in this discourse installs itself and produces real material effects, which social power structure and the prescribed gender norms also affect the relationship between characters. Power relations exist as the main female character, Amal has a certain relationship with the other main male characters and another female character. The power comes from the relation then brings oppression toward women. Power is compiled, established, and realized through certain knowledge and discourse. In addition, Amal’s appearance, which represents her gender identity, also indicates resistance toward the oppression she experienced. To conclude, subordination and oppression toward women are undeniable, as men are socially and culturally designed to be powerful. Meanwhile, women are powerless.